Private pension: Benefit expenditures - Mariusz Dybał (Economic and Environmental Studies (E&ES), 2017)
Private pension plans have been growing in importance in recent years as pension reforms all over the world have reduced public pension entitlements. The aim of the research study was to analyze the payments from private pension schemes in OECD countries. On the basis of studies it was found that: i) payments from private pension schemes were worth 1.6% of gross domestic product (GDP) on average in 2011 in the 26 OECD countries for which data are available; ii) payments from private pension schemes is equivalent to one-fifth of average public spending on retirement benefits (9,3%); iii) private-pension payments increased 38% faster than GDP between 1990 and 2011 on average, which is faster than public pension spending; iv) the countries (Korea, France, Finland) with the fastest growth in private pension payments tended to start from a low base, below 0.5% of GDP; v) many countries (Australia, Estonia, Mexico, Poland, the Slovak Republic and Sweden) introduced compulsory private pensions in the 1990s and many of them have yet to begin paying benefits; vi) the biggest flow of private-pension payments is in the countries (Netherlands, Switzerland, Iceland and Denmark) where private pensions were mandatory or quasi-mandatory; vii) in 17 OECD countries, private pensions were mandatory or quasi-mandatory in 2013.
Keywords: J32; J14; 330; pension spending; private pension plans; the pension system